2019
DOI: 10.1002/asia.201801689
|View full text |Cite
|
Sign up to set email alerts
|

AIE Fluorescent Gelators with Thermo‐, Mechano‐, and Vapochromic Properties

Abstract: A series of aggregation‐induced emission (AIE) fluorescent gelators (TPE‐Cn‐Chol) were synthesized by attaching tetraphenylethylene (TPE) to cholesterol through an alkyl chain. The properties of the gel, nano‐/microaggregate, and condensed phases were studied carefully. TPE‐Cn‐Chol molecules form AIE fluorescent gels in acetone and in DMF. Their fluorescence can be reversibly switched between the “on” and “off” states by a gel–sol phase transition upon thermal treatment. The AIE properties of aggregated nano‐/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…In particular, cholesterol can form stable gels by the synergistic effect of cooperative non-covalent bonding. Thus, vigorous research has been conducted, and application development aimed at optical function and collection performance has been explored in materials with cholesterol molecule [22]. Conversely, cholesterol has a rigid ring-fused structure and alkyl chain; therefore, it can be used as a substituent to introduce LC properties, and gelation ability can be expected without impairing the LC properties.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, cholesterol can form stable gels by the synergistic effect of cooperative non-covalent bonding. Thus, vigorous research has been conducted, and application development aimed at optical function and collection performance has been explored in materials with cholesterol molecule [22]. Conversely, cholesterol has a rigid ring-fused structure and alkyl chain; therefore, it can be used as a substituent to introduce LC properties, and gelation ability can be expected without impairing the LC properties.…”
Section: Introductionmentioning
confidence: 99%
“…[6,[20][21][22] The term piezofluorochromica ggregation-induced emission (PAIE) was even introduced. [23] Many pure organic mechanochromic materials with AIE-activem olecules were thus reported, [24][25][26][27][28][29][30][31] along with organoboron complexes. [32,33] Regarding metal-based compounds that combine AIE and mechanochromic properties, few studies have been reported, with examplesb ased on iridium(III), [34][35][36][37][38][39] cadmium(II), [40] zinc(II), [41,42] and gold(I) [43] complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 33 ] Obviously, the better the solubility of gelator, the higher the MGC and the worse gelation ability. As mentioned in the Introduction section, the length of flexible chains [ 13,34 ] and the number of substituents [ 14,15 ] play an important role in gel behavior. From those results, we can conclude that the more regular the molecular arrangement for gelator, the more difficult it is to form gel.…”
Section: Resultsmentioning
confidence: 99%